2022
DOI: 10.1007/s00702-022-02559-5
|View full text |Cite
|
Sign up to set email alerts
|

The pathobiological basis of depression in Parkinson disease: challenges and outlooks

Abstract: Depression, with an estimated prevalence of about 40% is a most common neuropsychiatric disorder in Parkinson disease (PD), with a negative impact on quality of life, cognitive impairment and functional disability, yet the underlying neurobiology is poorly understood. Depression in PD (DPD), one of its most common non-motor symptoms, can precede the onset of motor symptoms but can occur at any stage of the disease. Although its diagnosis is based on standard criteria, due to overlap with other symptoms related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 316 publications
0
14
0
Order By: Relevance
“…We speculated that pathological damage could involve reorganizing the hubs of the functional network during the early stages of DPD, particularly the temporal‐occipital regions engaged in receiving and processing information. Additionally, the present study also explored that DPD exhibits recruited hubs primarily in the limbic cortico‐basal ganglia circuit with regional dysfunction mentioned in previous DPD studies (Jellinger, 2022). However, the current study explored no correlation between the regional topological properties and depressive symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…We speculated that pathological damage could involve reorganizing the hubs of the functional network during the early stages of DPD, particularly the temporal‐occipital regions engaged in receiving and processing information. Additionally, the present study also explored that DPD exhibits recruited hubs primarily in the limbic cortico‐basal ganglia circuit with regional dysfunction mentioned in previous DPD studies (Jellinger, 2022). However, the current study explored no correlation between the regional topological properties and depressive symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that the occurrence of dPD is associated with dysfunction of brain neurotransmitters, blockade of neurotransmitter signal transduction pathways, and neurodegeneration. [ 46 ] Deficiency of dopamine, norepinephrine and serotonin may be happened in the substantia nigra, striatum, limbic system and raphe nuclei. Dopaminergic neuron degeneration is found in the substantia nigra pars compacta and ventral tegmental area of midbrain, serotonergic and adrenergic neurons in the raphe nuclei and hypothalamus also have morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Mood disorders, sleep disorders, and PD may share some common pathogenic mechanisms, including degeneration or dysfunction of dopaminergic, serotonergic, and noradrenergic circuits [19][20][21] . PD is de ned by loss of dopaminergic neurons in striatonigral pathway, with relative preservation of the mesocortical and mesolimbic pathways.…”
Section: Discussionmentioning
confidence: 99%